Biophysical analysis of Pseudomonas-phage PaP3 small terminase suggests a mechanism for sequence-specific DNA-binding by lateral interdigitation. Issue 20 (30th October 2020) - Niazi, Marzia; Florio, Tyler J; Yang, Ruoyu; Lokareddy, Ravi K; Swanson, Nicholas A; Gillilan, Richard E; Cingolani, Gino
Abstract: The genome packaging motor of tailed bacteriophages and herpesviruses is a powerful nanomachine built by several copies of a large (TerL) and a small (TerS) terminase subunit. The motor assembles transiently at the portal vertex of an empty precursor capsid (or procapsid) to power genome encapsidation. Terminase subunits have been studied in-depth, especially in classical bacteriophages that infect Escherichia coli or Salmonella, yet, less is known about the packaging motor of Pseudomonas -phages that have increasing biomedical relevance. Here, we investigated the small terminase subunit from three Podoviridae phages that infect Pseudomonas aeruginosa . We found TerS is polymorphic in solution but assembles into a nonamer in its high-affinity heparin-binding conformation. The atomic structure of Pseudomonas phage PaP3 TerS, the first complete structure for a TerS from a cos phage, reveals nine helix-turn-helix (HTH) motifs asymmetrically arranged around a β-stranded channel, too narrow to accommodate DNA. PaP3 TerS binds DNA in a sequence-specific manner in vitro . X-ray scattering and molecular modeling suggest TerS adopts an open conformation in solution, characterized by dynamic HTHs that move around an oligomerization core, generating discrete binding crevices for DNA. We propose a model for sequence-specific recognition of packaging initiation sites by lateral interdigitation of DNA.